Menjadi Sociopreneur Muda: Studi Kasus Momsociopreneur ‘Sanggar ASI' - Dewi Cahyani Puspitasari (Jurnal Studi Pemuda, 2018)
The existence of social entrepreneurship movement then might be the answer to generate the entrepreneurs capable of identifying new ways, establishing new business to generate social values and coping with various social issues. The youth, in this case, becomes the drive of social entrepreneurship movement. They have an entrepreneurship spirit based upon their competence not only to build a business and obtain the profit for themselves but also to run their business for the improvement of social and economic state of society. This research is an initial study focused on the individual to identify the successful characters and the innovative process of the young sociopreneur in initiating and developing a social business. This study used a method of case study with the main research subject of momsociopreneur ‘Sanggar ASI. The primary and secondary. The results of this study showed that the process to be sociopreneur required various skills and competences correlated to the performance of the pioneering social business. From the beginning, confidence becomes the main power that is able to mobilize to actively act in solving the social problems such as the failure of breastfeeding among mothers or the lack of breastfeeding. The preferences of values and norm can be internalized in all social business including in work place, partner network, clients or community as the beneficiaries of social service and family institution. In the process of developing their social business, the sociopreneurs have an adaptive competence in responding any innovation. Thus, momsociopreneur ‘Sanggar ASI can be the role model for the youth especially for females attempting to grow their self-potential to participate and answer the problems and social needs of community.